Soy Rene, el nino - Colato Lainez, Rene; Graullera Ramirez, Fabiola (Houston, Tex. : Pinata Books/Arte Pubiico Press, 2005)
When Rene learns that in the United States his name is also a girl's name, he does some research and relates the name's meaning and letters to his homeland of El Salvador and the things that make him special.
Accelerated Reader
Keywords: Salvadoran Americans -- Juvenile fiction; Names, Personal -- Juvenile fiction; Schools -- Juvenile fiction; Bilingualism -- Juvenile fiction; Spanish language materials -- Bilingual -- Juvenile literature; Nombres personales -- Novela juvenil; Escuelas -- Novela juvenil; Materiales bilingues en espanol -- Literatura juvenil; Salvadoreno-americanos -- Novela juvenil; #OwnVoices - Latinx